Hubungan Antara Lama Demam dengan Hasil Pemeriksaan Profil Darah pada Pasien Demam Berdarah Dengue - Faisal abdul Masykur (Jurnal Ilmu Medis Indonesia, 2022)
Purpose: can provide an overview of the blood profile of the duration of fever in dengue hemorrhagic fever. Methodology: The method used is a literature study from various national and international journals. This method is used with the aim of summarizing a current topic in order to increase an understanding. Results: In DHF patients, thrombocytopenia occurs, generally thrombocytopenia on the 3rd to 8th day, there is a decrease in platelets below 100,000, an increase in hematocrit > 20% of the initial hematocrit, generally starting on the 3rd day of fever. IgM appears earlier since the onset of fever, which is around day 3, while IgG can appear more than 7 days from the onset of fever. As for secondary infections, IgG can appear earlier, around the 1st day of fever, which can be followed by the appearance of IgM. Limitations: This article is only a review of several other articles, not doing research directly. Contribution: With proper examination, it is hoped that cases of dengue hemorrhagic fever can be managed quickly.